Muhasabah Sebagai Upaya Rehabilitasi Eks-Pecandu Narkoba Di Yayasan Suci Hati Padang - Ahmad Saefulloh (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2018)
This paper aims to provide educational steps to institutions and agencies that implement rehabilitation programs of active or passive addicts of narcotics users. Institutions that make efforts to cure victims of drug abusers tend to pay less attention to the precise step that is the right step to do before the provision of materials or other religious approach programs. Drug Abuse has dangerous consequences, so the problem of drugs is classified into extra ordinary problems, ie problems that have no end. Various efforts have been made by the Government from preventive to rehabilitative. However, the problem has not yet been resolved, it increases in the next year. This mitigation effort can not be fully burdened to the government only, there needs to be synergy between government, society, parents, and related institutions in their field. This effort is one form of mutual concern that has been listed in the Narcotics Act, and planting aqidah through this muhasabah program as a preventive effort that can be done by institutions and NGOs in charge of rehabilitation of addicts. Research that the authors do is a qualitative type with qualitative descriptive analysis approach. The data of this study were collected through interviews and document analysis. The results show that there is a significant change of conscious attitude in receiving materials, direction, and other debriefing during rehabilitation process.